The crushing characteristics of reinforced Nomex honeycomb. (October 2018) - Alia, RA; Rao, S; Umer, R; Zhou, J; Zheng, C; Guan, Z; Cantwell, WJ
A Nomex honeycomb core has been reinforced with small diameter composite rods and tubes in order to enhance its compression properties and energy-absorbing characteristics. The influence of the areal density of the rods and tubes on the strength and energy-absorbing properties of the reinforced honeycomb was investigated by introducing increasing numbers of rods/tubes in square samples with bonded composite skins. An initial series of crushing tests on arrangements of small tubes and rods resulted in a stable model of failure yielding specific energy absorption values of approximately 45 kJ/kg for the tube and rod-based structures. A subsequent observation of the failed tubes highlighted the similar failure processes to those observed previously following the tests on much larger composite cylinders. Mechanical tests on the Nomex cores have shown that the compression strength and energy-absorbing characteristics of the reinforced honeycombs increase rapidly with increasing composite reinforcement. At low and intermediate values of core density, the rod and tube-reinforced cores exhibited similar properties, in terms of their compression strengths and specific energy absorption, an effect that is likely to be due to the dominance of the heavier Nomex core in these samples. At higher densities, the rod-reinforced systems tended to out-perform their tube-reinforced counterparts. Tests at impact rates of strain have shown that the compression strength and energy-absorbing capabilities of the reinforced cores are higher under the dynamic conditions, with the rod-reinforced cores offering values of specific energy absorption as high as 78 kJ/kg.